Hydrological and Isotopic Variability of Perched Wetlands on North Stradbroke Island (Minjerribah), Australia: Implications for Understanding the Effects of Past and Future Climate Change - Tyler, Jonathan J.; Marshall, Jonathan C.; Schulz, Cameron; Barr, Cameron; Hofmann, Harald; Blessing, Joanna J.; McCoy, Kelsey; McGregor, Glenn B.; Tibby, John (Frontiers in Environmental Science, 2022)
Over the first two decades of the 21st century, many wetlands in eastern Australia exhibited declining water levels, causing concern for communities and environmental managers and raising questions about the roles of climate change and other human activity in these water level declines. In this context we examine the causes of water level variability in four wetlands on North Stradbroke Island (Minjerribah), in the humid subtropics of south-eastern Queensland (Australia), using a combination of hydrological and water isotope monitoring and modelling. North Stradbroke Island has a high concentration of wetlands perched above the regional water table, with cultural and ecological significance, and value for palaeoclimate research. From 2015 to 2019, wetland water depths decreased markedly at all sites, coinciding with increases in oxygen isotope ratios in surface waters. The data indicate that climate, specifically a decrease in precipitation relative to evaporation, was responsible for those declining water levels, and that groundwater extraction did not play a critical role. At two of the sites - both palustrine wetlands - declining surface water levels led to intermittent connectivity with the local perched aquifers. At the other two sites, which are both shallow lakes, the surface waters were constantly fed by perched groundwater. The hydrology of the two lakes was modelled using simple mass balance. However, in order to accurately model lake level change, it was necessary to vary catchment runoff and lake outflow via groundwater through time, highlighting complexity in projecting future hydrological change in these lakes. The long term resilience of these lakes depends on a combination of rainfall regime and the balance between catchment runoff and groundwater throughflow, the future of which is highly uncertain. As a consequence, continued efforts to project future hydroclimate and to model the complex hydrology of subtropical wetlands are essential.